Performance analysis of rapeseed-mustard crop under different agro-climatic conditions of Jammu Division of J & K state - KUMAR, RAKESH; SLATHIA, P S; PESHIN, RAJINDER; GUPTA, S K; GUPTA, S K; NAIN, M S (The Indian Journal of Agricultural Sciences, 2023)
Rapeseed-mustard is the second most important edible oilseed crop in India after groundnut. It has to play a significant role in making India self-reliant in oilseed sector. At present contribution of India to the world acreage and production is 19.29% and 11.12% respectively. Productivity of rapeseed mustard in J & K is 6.98 q/ha which is 37.72% of global productivity and 67.85% of national productivity. Keeping in view low productivity of rapeseed mustard crop in J & K state, a study was undertaken with randomly selected 200 rapeseed mustard growers 100 each from subtropical and temperate zone of Jammu division covering Jammu, Samba, Reasi and Doda districts to ascertain the performance of rapeseed mustard crop under farmer field conditions. Multiple linear regression model was applied to work out the factors affecting productivity of rapeseed mustard crop. The results revealed that proper irrigation, spray of insecticide, proper sowing method, thinning, use of basal dose of urea at sowing time and proper weed management significantly affected the productivity of Indian mustard (Brassica juncea) with R2 value 0.534. The drivers of productivity of gobhi sarson (Brassica napus) were proper time of sowing and irrigation with R2 value 0.253 while use of phosphorus and irrigation at proper time were found to be significantly affecting the productivity of toria (Brassica rapa) with R2 value 0.757. The factors affecting the productivity of hybrid gobhi sarson were proper weed control and knowledge about different production recommendations with R2 value 0.080.